Keberlanjutan Wilayah: Keterkaitan Desa-Kota dalam Aktivitas Minapolitan di Kabupaten Malang - Wawargita Permata Wijayanti; Rahmat Aris Pratomo (P4W LPPM IPB, 2019)
Regional Sustainability: Rurban Linkage on the Context of Minapolitan Activity in Malang Regency A rurban linkage is one of the aspects to achieve sustainable regional development, which emphasizes on balancing functions and interrelationships between rural and urban. This linkage is very important to increase the chain of economic activity, including on developing minapolitan area. However, due to bias of rural and urban function, the linkage between urban and rural became difficult to be actualized, thus creates an increasing gap between the regions. This research aims to determine the typology of rural and urban and its relationship in minapolitan activity in Malang Regency. The analysis is carried out using cluster analysis in order to determine rural and urban typology in Malang Regency. Furthermore, it is continued by using rurban linkage matrix for mapping linkages of minapolitan activities. Results show that majority of districts (20 out of 33 districts) in Malang Regency are included in the category of highly rural and only 3 districts have strong urban characteristics (rurban type A). In relation to the minapolitan, rurban linkage has begun to be well formed on fishing activity. Meanwhile, linkage in aquaculture is hard to be formed due to the development of minapolitan activity that tend to be stagnant, specifically only developing at producing areas. Findings can be used as consideration for formulating rurban linkage strategies on developing minapolitan activity.